Women on Board: The Impact on Financial Performance of Companies Listed on Bursa Malaysia - MASLINA AHMAD; SADIK ABUBAKAR ABDIRAHMAN; HAIRUL AZLAN ANNUAR (Asian Journal of Accounting Perspectives, 2024)
Research aim: This study aims to investigate the link between women representation as board members and Bursa Malaysia-listed companies’ financial performance. Design/ Methodology/ Approach: Data was obtained from the Bursa Malaysia website on the 100 leading public listed companies (PLCs). The data covers the period between 2016 and 2018. The association between the dependent and independent variables was evaluated using panel data regression analyses. Research finding: The findings indicate a negative association between the representation of women on directorial boards and firm financial performance. Conversely, positive associations were found between women on audit committees and firm performance, and when women serve as CEOs or board chairpersons. The study also finds that women directors with accounting and finance backgrounds, as well as their age, tenure, and independence have no significant association with firm performance. Theoretical contribution/ Originality: The main academic contribution this study makes is evidence that women on boards was an influential factor after 2016; by this year, Malaysian listed companies were to have implemented this policy effectively. Practitioner/ Policy implication: The results of the study showed that firm performance may be enhanced when women fill positions on audit committees or as CEOs or chairpersons. This may motivate listed firms in Malaysia to appoint more qualified women as members of the boards not only to adhere to the government policy, but also to benefit in terms of financial performance. Research limitation: The study only examines the top 100 PLCs, which may affect the generalisation of the results. Second, the research only covered the years 2016 to 2018, so the study might not fully illustrate the actual long-term impact that women directorial board members have on firm performance. Furthermore, this paper does not examine the critical mass of women directors in depth, although the amount of women board members needed to have a major effect will be determined by this.